I'm trying to find the series representation of $ f(x)=\int_{0}^{x} \frac{e^{t}}{1+t}dt $. I have found it using the Maclaurin series, differentiating multiple times and finding a pattern. But I think there must be an easier way, using the power series of elementary functions. I know that $e^{x}=\sum_{0}^{\infty}\frac{x^{n}}{n!}$ and $\frac{1}{1+x}=\sum_{}^{\infty}(-1)^{n}x^{n}$ but I don't know how to use it here. Thanks

(Don't hesitate to correct my English)


$$e^x=\sum_{n\ge 0}\frac{x^n}{n!}$$

$$\frac{1}{x+1}=\sum_{n\ge 0}(-1)^nx^n$$

$$\frac{e^x}{x+1}=\sum_{b\ge 0}\sum_{a\ge 0} \frac{(-1)^b}{a!}x^{a+b}$$

$$\frac{e^x}{x+1}=\sum_{n\ge 0}\sum_{a+b=n}_{a,b\ge 0} \frac{(-1)^b}{a!}x^{a+b}$$

$$\frac{e^x}{x+1}=\sum_{n=0}^\infty x^n(-1)^n(\sum_{k=0}^n (-1)^{k}\frac{1}{k!})$$

Now the interesting thing about these coefficients above that are given in the form of partial sums is that it turns out that we have:

$$\sum_{k=0}^n\frac{(-1)^k}{k!}=\frac{1}{e}+\frac{1}{n!}(\frac{(-1)^n+1}{2}-\{ \frac{n!}{e}\})$$

Where {.} is the fractional part function.

So that we get:

$$\frac{e^x}{x+1}=\sum_{n=0}^\infty x^n(-1)^n(\frac{1}{e}+\frac{1}{n!}(\frac{(-1)^n+1}{2}-\{ \frac{n!}{e}\}))$$

$$=\frac{1}{e}\sum_{n=0}^\infty x^n(-1)^n+\sum_{n=0}^\infty x^n(-1)^n\frac{1}{n!}(\frac{(-1)^n+1}{2}-\{ \frac{n!}{e}\})$$

$$=\frac{1}{e(x+1)}+\frac{1}{2}\sum_{n=0}^\infty\frac{x^n}{n!}(1+(-1)^n)-\sum_{n=0}^\infty\frac{x^n(-1)^n}{n!}\{ \frac{n!}{e}\}$$ $$=\frac{1}{e(x+1)}+\frac{e^x+e^{-x}}{2}-\sum_{n=0}^\infty\frac{x^n(-1)^n}{n!}\{ \frac{n!}{e}\}$$ $$=\frac{1}{e(x+1)}+\frac{e^x+e^{-x}}{2}+\sum_{n=0}^\infty\frac{x^n}{n!}\{ \frac{n!}{e}\}(-1)^{n+1}$$

Now integrating term by term gives,

$$\int_{0}^x \frac{e^t}{1+t} dt=\frac{\ln(x+1)}{e}+\frac{e^x-e^{-x}}{2}+\sum_{n=0}^\infty\frac{x^{n+1}}{(n+1)!}\{ \frac{n!}{e}\}(-1)^{n+1}$$

Thus for all $|x|<1$ the following expansion holds:

$$f(x)=\int_{0}^x \frac{e^t}{1+t} dt=\frac{\ln(x+1)}{e}+\frac{e^x-e^{-x}}{2}+\sum_{n=1}^\infty\frac{(-x)^n}{n!}\{ \frac{(n-1)!}{e}\}$$

Also pretty off topic, but the positive $n^{\text{th}}$ coefficients that took the form of partial sums in our first list of series manipulations above correspond to solutions to the hat-check problem when $n$ hats are being considered.


A hint: if $$g(t) = \sum_{n=0}^\infty a_nt^n$$ and $$h(t) = \sum_{n=0}^\infty b_nt^n$$ then $$g(t)h(t) = \sum_{n=0}^\infty\left(\sum_{k=0}^n a_kb_{n-k}\right)t^n.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.